Analysis of the Preparedness of the Village Government and Community in Facing Drought Disasters in Sumberharjo Village, Sumberrejo Sub District, Bojonegoro Regency - Nisa, Nur Afiza Sholihatun (SERUNAI, 2022)
This research aimed to determine whether the role of village government and community preparedness had a significant influence partially and simultaneously on community preparedness in facing drought disasters in Sumberharjo Village, Sumberrejo Sub District, Bojonegoro Regency. This research was conducted in Sumberharjo Village, Sumberrejo Sub District, Bojonegoro Regency from August to October 2023. The population consisted of 1308 households in Sumberharjo Village. For the government role variable, all village officials were included, and the sample in this research was determined using the Slovin formula, resulting in 92 samples. The data collection technique used was incidental. The data analysis technique used in this research was quantitative descriptive with data collected in the form of questionnaires, observations, and documentation. The results of the data analysis testing in this research discuss the preparedness of the village government and community in dealing with drought disaster mitigation in Sumberharjo Village, Sumberrejo Sub District, Bojonegoro Regency.